Music therapy handbook - Wheeler, Barbara L. (New York, NY : The Guilford Press, 2015)
This groundbreaking volume provides a comprehensive overview of contemporary music therapy, from basic concepts to emerging clinical approaches. Rich case examples illustrate ways in which this powerful modality can help people of all ages to develop skills, adapt their behavior, and overcome obstacles in their lives. Expert contributors discuss the broad array of practices in the field, review the burgeoning research literature, and offer in-depth clinical guidance. Innovative applications are presented for children and adults in mental health, medical, and community settings. Part I explains the foundations of music therapy and examines professional issues. Topics include assessment and intervention methods, music and the brain, cultural issues in treatment, and evidence-based practice. Part II focuses on theoretical orientations and approaches. Contributors demonstrate how music therapists draw on elements of psychodynamic, humanistic, and cognitive-behavioral therapy. Also described are models developed specifically for music therapy, such as the Nordoff-Robbins model, the book's largest section, showcases technique and strategies for working with particular clinical populations. Chapters on children and adolescents cover intellectual disabilities, autism spectrum disorder, speech and language disorders, and more. Chapters on adults cover a range of areas where music therapy has been shown to be especially effective, such as addictions, trauma, bereavement, and work with older adults. Several chapters address the growing area of medical music therapy. As authoritative resource, the Handbook shows how music can be used by a broad range of mental health and medical professionals working with children and adults. It belongs on the shelves of music, movement, art, and play therapists; clinical pssychologists; social workers; counselors; psychiatrists; and nurses, as well as clinical graduate students.-- from dust jacket.
Music therapy as a profession / Barbara L. Wheeler -- A history of music therapy / William Davis and Susan Hadley -- Aesthetic foundations of music therapy : music and emotion / James Hiller-- Music therapy and the brain / Concetta M. Tomaino -- Music therapy and cultural diversity / Seung-A Kim and Annette Whitehead-Pleaux -- Ethics in music therapy / Debbie Bates --Music therapy assessment / Anne W. Lipe -- Music therapy research / Debra S. Burns and Anthony Meadows -- Evidence-based practice in music therapy / Felicity A. Baker -- Music therapy methods / Susan Gardstrom and Suzanne Sorel -- Psychodynamic approaches / Connie Isenberg -- Humanistic approaches / Brian Abrams --Cognitive-behavioral approaches / Suzanne Hanser -- Developmental approaches / Cynthia A. Briggs -- Nordoff-Robbins music therapy / Nina Guerrero, David Marcus, and Alan Turry -- The Bonny method of guided imagery and music / Madelaine Ventre and Cathy H. McKinney -- Analytical music therapy / Benedikte B. Scheiby --Neurologic music therapy / Corene P. Hurt-Thaut and Sarah B. Johnson -- Community music therapy / Brynjulf Stige -- Music therapy in expressive arts / Margareta Wärja -- Music therapy for developmental issues in early childhood / Marcia Humpal --Music therapy for children with intellectual disabilities / Beth McLaughlin and Ruthlee Figlure Adler -- Music therapy for children with autism spectrum disorder / John A. Carpente and A. Blythe LaGasse -- Music therapy for children with speech and language disorders / Kathleen M. Howland -- Music therapy for children with sensory deficits / Greta E. Gillmeister and Paige A. Robbins Elwafi -- Music therapy in the schools / Katrina Skewes McFerran -- Music therapy for adults with mental illness / Gillian Stephens Langdon -- Music therapy in addictions treatment / Kathleen M. Murphy -- Music therapy for older adults / Hanne Mette Ridder and Barbara L. Wheeler -- Music therapy for women survivors of domestic violence / Elizabeth York and Sandra L. Curtis -- Music therapy for survivors of traumatic events / Ronald M. Borczon -- Music therapy for grief and loss / Robert E. Krout -- Music therapy in the neonatal intensive care unit / Helen Shoemark and Deanna Hanson-Abromeit -- Medical music therapy for children / Joanne Loewy -- Medical music therapy for adults / Carol Shultis and Lisa Gallagher -- Music therapy for adults with traumatic brain injury and other neurological disorders / Jeanette Tamplin -- Music therapy at the end of life / Clare O'Callaghan, Lucy Forrest, and Yun Wen.
Includes bibliographical references (pages 479-480) and index.
Keywords: Music Therapy